Optimization of triploid induction by the use of 6-DMAP for the oyster Crassostrea gigas (Thunberg) - Gerard, Andre; Naciri, Yamama; Peignon, Jean-marie; Ledu, Christophe (1994)
A novel method using 6-dimcthylaminopurinc (6-0MAP) has recently been demonstrated to be a good triploid inductor for bivalve molluscs. The effects of 6-DMAP concentration, timing of treatment after fertilization and treatment duration on survival and triploid induction of Crassostrea gigas (Thunberg) embryos were examined. An influence of sperm concentration was also detected and discussed. Survival to D-stage was inversely related to 6-DMAP concentration and the percentage of triploids was shown to be 6-DMAP dose dependent. Two optimal moments for treatment application were determined corresponding to extrusions of the first and second polar bodies. Optimal treatment of 450 µmol/l 6-DMAP beginning 15 min after fertilization over a 10 min period yielded mean survival to D-stage of 64% with a mean of 85% triploid production. As a comparison, a sample treated with 1mg/l of cytochalasin B (CB), 20 min after fertilization over a 15 min period, yielded a mean survival to D-stage of only 36% with a mean of 95% triploid production. The advantages of 6-DMAP over CB arc clearly identified: this chemical is not carcinogenic, cheaper than cytochalasin B and much easier to use as it is water soluble